2018
DOI: 10.1136/bmjopen-2017-020380
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of interventions to support the careers of women in academic medicine and other disciplines

Abstract: ObjectiveTo summarise quantitative evaluations of interventions designed to support the careers of women in academia of any discipline.MethodA systematic search of English entries in PubMed, CINAHL and Google Scholar was conducted in September 2017. Methodological quality of the studies was independently assessed by two authors using the Joanna Briggs Institute quality appraisal checklists. Meta-analysis was not possible due to heterogeneity in methods and outcomes; results were synthesised and displayed narra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
99
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(102 citation statements)
references
References 44 publications
(75 reference statements)
3
99
0
Order By: Relevance
“…Prior literature has highlighted successful programmatic interventions for the advancement of women in academic medicine . A literature review by Laver and colleagues summarized findings, citing 18 studies that evaluated dedicated programming for women in academic medicine. Many programs were tailored to women at specific career stages and most commonly focused on mentoring, education, and professional development.…”
Section: The Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior literature has highlighted successful programmatic interventions for the advancement of women in academic medicine . A literature review by Laver and colleagues summarized findings, citing 18 studies that evaluated dedicated programming for women in academic medicine. Many programs were tailored to women at specific career stages and most commonly focused on mentoring, education, and professional development.…”
Section: The Frameworkmentioning
confidence: 99%
“…Data on more objective outcomes, i.e., promotion and retention, were mixed, pointing to the need for further research on institutional‐level strategies that would increase the promotion and advancement of women. Not surprisingly, a few studies assessed educational interventions on gender bias in hiring practices and demonstrated an enhanced awareness of gender bias after program implementation . Overall, some of the strategies described in the literature were flawed as they placed additional burden on individual faculty rather than targeting institutional‐level strategies.…”
Section: The Frameworkmentioning
confidence: 99%
“…1,9 Research has also shown that women in academia lack adequate mentorship and role models, which are known barriers to professional development and promotion for women. 17,18 Therefore, the presence of women in important and influential positions within the health care field is paramount to ensuring that mentoring opportunities are available for other women with similar aspirations. The National Research Mentoring Network and similar consortiums have attempted to facilitate diversity and inclusivity among biomedical professions.…”
Section: Medicinementioning
confidence: 99%
“…However, their systematic review also revealed that it is important how these interventions are delivered. Bottom-up approaches, which place the onus largely on the individual wishing to progress their career, were less successful [16]. Our review aims to expand on these findings by using a more comprehensive search strategy and taking into account discrimination and biases based on characteristics other than gender, as well.…”
Section: Introductionmentioning
confidence: 99%